BOUNDARY VALUE PROBLEM FOR A PARTIAL DERIVATIVE EQUATION OF PARABOLIC TYPE WITH TWO LINES OF DEGENERACY - Sharipov J. I. (European Science Publishing, 2024)
This paper examines the edge problem for a partial differential equation of parabolic type with two lines of degeneracy, a representation of the solution is obtained, an a priori estimate of the solution is derived, theorems are obtained that prove the uniqueness and conditional stability on the correctness set of the solution.
Keywords: ill-posed problem, a priori estimate, correctness set, uniqueness, conditional stability.